Trends in estrogen and progesterone receptors in prostate cancer: a bibliometric analysis - Liao, Wenqiang; Sui, Xuxia; Hou, Gaoming; Yang, Mei; Lin, Yuxue; Lu, Junjie; Yang, Qingtao (Frontiers in Oncology, 2023)
The bibliometric analysis aims to identify research trends in estrogen receptor (ERs) and progesterone receptor (PRs) in prostate cancer (PCA), and also discuss the hotspots and directions of this field. 835 publications were sourced from the Web of Science database (WOS) from 2003 to 2022. Citespace, VOSviewer, and Bibliometrix were used for the bibliometric analysis. The number of published publications increased in early years, but declined in the last 5 years. The United States was the leading country in citations, publications, and top institutions. Prostate and Karolinska Institutet were the most publications of journal and institution, respectively. Jan-Ake Gustafsson was the most influential author based on the number of citations/publications. The most cited paper was "Estrogen receptors and human disease" by Deroo BJ, published in the Journal of Clinical Investigation. The most frequently used keywords were PCA (n = 499), gene-expression (n = 291), androgen receptor (AR) (n = 263), and ER (n = 341), while ERβ (n = 219) and ERα (n = 215) further emphasized the importance of ER. This study provides useful guidance that ERα antagonists, ERβ agonists, and the combination of estrogen with androgen deprivation therapy (ADT) will potentially serve as a new treatment strategy for PCA. Another interesting topic is relationships between PCA and the function and mechanism of action of PRs subtypes. It is worth mentioning that the keywords "PCA," "gene expression," "AR," "ER," and "ER-related subtypes" seemed to be popular in the past. And now "estrogen" and "ADT" deserves an in-depth discussion of the hot issues.